Student Self-Assessment Re-Assessed - Weiss, Katharina (Journal of Academic Writing, 2018)
In a student-centered classroom, learners have to be actively involved both in learning and assessment, which in itself needs to become a learning tool. Therefore, students need to understand and be given the opportunity to apply assessment criteria themselves. Through self-assessment of their writing, they enhance their self-awareness and become autonomous learners capable of self-improvement and meta-cognition (Liang 2014, Nielsen 2012). Self- and peer assessment are helpful tools that have been discussed in the literature, but the reliability of self-assessment is still debated (see for example Birjandi and Tamjid 2012, Matsuno 2009, Poehner 2012). The present study adds to the existing research by offering data that is not based on observation, but stems from a comparison of self- and instructor assessment where both parties used the same specific assessment rubrics. Assigning numerical values to the rubrics allowed for quantitative results. The data was collected in four classes of students in a course called ‘Introduction to Academic Writing’ at Deree - The American College of Greece. The outcome of the study did not confirm expectations with regard to reliability of self-assessment, and recommendations for future rubric-based studies are included. Self-assessment should be used as a formative and diagnostic learning tool, especially for weaker students, to foster development of learner autonomy.